2019
DOI: 10.1177/0961203319890681
|View full text |Cite
|
Sign up to set email alerts
|

Initial renal histology and early response predict outcomes of Brazilian lupus nephritis patients

Abstract: Objective We analyzed baseline and follow-up characteristics related to poorer renal outcomes in a Brazilian cohort of admixture race patients with lupus nephritis. Methods Overall, 280 outpatients with a diagnosis of systemic lupus erythematosus and previous kidney biopsy of lupus nephritis were recruited from August 2015 to December 2018 and had baseline laboratory and histologic data retrospectively analyzed; patients were then followed-up and data were recorded. The main outcome measure was the estimated g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 39 publications
3
9
0
Order By: Relevance
“…Recent studies indicated that the rate of CRR varied between 20 and 65%, and the rate of PRR is between 18 and 27%. 10 , 21 , 28 Renal response rates obtained in our study were rather consistent with previous reports. Factors predicting CRR during the 2-year follow-up were also analyzed.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Recent studies indicated that the rate of CRR varied between 20 and 65%, and the rate of PRR is between 18 and 27%. 10 , 21 , 28 Renal response rates obtained in our study were rather consistent with previous reports. Factors predicting CRR during the 2-year follow-up were also analyzed.…”
Section: Discussionsupporting
confidence: 93%
“… 30 In a study regarding the histopathologic findings of LN, class IV and chronic interstitial damage at initial renal biopsy were associated with worse renal outcomes. 21 In our study, although all patients who did not respond to treatment, developed ESRD, and died during the 2-year follow-up were in the proliferative LN group, the complete or partial renal response rates were similar in both groups. This situation may be explained by the small number of patients in the non-proliferative group.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…39 In Brazil, chronic glomerulopathies represent a major cause of ESRD, accounting for 11% of dialysis patients. 40 A study conducted in the northeastern region demonstrated that secondary glomerulopathies, including LN, were present in 42% of cases.…”
Section: Histological Classifications In Brazilmentioning
confidence: 99%
“…In our study, 22% of patients reached the composite renal outcome (stage 3–4 CKD or ESRD) in a median follow-up time of 100 months. Several studies have identified baseline parameters as predictors of long-term renal prognosis, such as creatinine, proteinuria, hypertension, activity and chronicity index [ 43 , 44 ], while others [ 15 , 16 , 18 , 28 , 40 , 44 , 45 ] highlight the importance of renal parameters at 12 months as single variables (i.e., proteinuria <0.7 g/day or <0.8 g/day) or as composite endpoint (i.e., renal response). Renal response definition, however, is not uniform across studies.…”
Section: Discussionmentioning
confidence: 99%